Intrahepatic Cholestasis of Pregnancy in Women With Twin Pregnancy. (28th September 2016) - Shan, Dan; Hu, Yayi; Qiu, Peiyuan; Mathew, Bechu Shelley; Chen, Yun; Li, Si; Hu, Yuan; Lin, Lijun; Wang, Zhi; Li, Luping
Abstract : The aim of the present work was to determine maternal and fetal outcomes of intrahepatic cholestasis of pregnancy (ICP) in twin pregnancies. All twin pregnancies delivered above 28 gestational weeks in West China Second University Hospital from January 2013 to May 2015 were included. Data on maternal demographics and obstetric complications together with fetal outcomes were collected. The risk of adverse maternal and fetal outcomes were determined in relation to ICP by crude odds ratios (OR) and adjusted ORs (aOR) with 95% confidence intervals (CI). Subgroup analysis concentrated on the effect of assisted reproductive technology (ART), ICP severity, and onset time. A total of 1, 472 twin pregnancies were included, of which 362 were cholestasis patients and 677 were conceived by ART. Higher rates of preeclampsia (aOR 1.96; 95% CI 1.35, 2.85), meconium-stained amniotic fluid (aOR 3.10; 95% CI 2.10, 4.61), and preterm deliveries (aOR 3.20; 95% CI 2.35, 4.37) were observed in ICP patients. Subgroup analysis revealed higher incidences of adverse outcomes in severe and early onset ICP groups. In conclusion, adverse maternal and fetal outcomes were strongly associated with ICP in twin patients. Active management and close antenatal monitoring are needed, especially in the early onset and severe groups.